THE EFFECT OF ANIMATED VIDEO HEALTH EDUCATION ON ANEMIA PREVENTION WITH THE KNOWLEDGE OF ADOLESCENT GIRLS AT KESTARIAN 1 SEMARANG HIGH SCHOOL - Mariyana, Widya; Gloria, Fransisca (Lux Mensana: Journal of Scientific Health, 2025)
Introduction. Anemia is a condition of the body where the level of hemoglobin (Hb) in the blood is less than normal. In general, anemia occurs more often in young women than in men. Anemia in adolescents occurs due to nutritional deficiencies, especially iron and folic acid. This lack of intake is due to low knowledge or wrong perceptions about diet without considering the body's need for macro and micro substances. The impact of anemia on teenagers can be a decrease in academic achievement and susceptibility to disease. Health education media with animated videos can have advantages over other media because they are more interesting. After all, it is in audiovisual form, the images displayed are more interesting and easier for teenagers to accept and understand. Method. The method used was a nonrandomized quasi-experimental pretest-posttest one-group design. The sample in this study consisted of 60 respondents, who were taken by purposive sampling. Respondents were given education about anemia using animated video media where before and after the intervention they were given a pre-test and post-test. Bivariate analysis test using the Wilcoxon test to determine the difference in mean knowledge before and after intervention. Result&Analysis. There is an influence of providing education using animation media on increasing knowledge of young women about anemia at Kestrian 1 High School Semarang, shown by the significance value of p-value of 0.000, which means the p-value is <0.05. Discussion. Animated video media has the effect of increasing young women's knowledge about preventing and treating anemia.